Analisis Strategi Promosi Digital Melalui Editing Video Capcut Pada CV. Affection Group - Anggi Irwanda; Fani Khoirotunnisa (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2025)
Digital technology development encourages businesses to utilize social media as an effective promotional tool, including through video-based content. This research aims to analyze digital promotion strategies through video. editing using the CapCut application at CV. Affection Group, identify supporting and inhibiting factors, and determine the influence of video editing quality on improving digital promotion effectiveness. This study uses a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. The results show that CapCut plays an important role in producing promotional video content for Instagram and TikTok due to its complete features and ease of use. Documentation insights indicate that one Instagram Reel achieved 370,000 views and 3,200 likes, while a TikTok video received 11.6K views and 1,002 likes, proving that video quality significantly affects audience engagement and promotional reach. Supporting factors include adequate editing features and the growing need for visual content, while the main challenges are teamwork collaboration and limited access to CapCut Pro. Overall, video-based digital promotion strategies are proven effective in increasing visibility and building client trust in CV. Affection Group.